Robotics and Biomedical Innovative Applications in Public Health during the COVID-19 Pandemic - Cornejo, José (2020)
In the current situation of the large-scale spread of COVID-19, whereas contagion increases, the role of robots (designed with Teleoperation and Artificial Intelligence technology) in society becomes essential, because they need to be used in hospital settings, urban environment, and also using Telemedicine consultancy to have access to all communities in the world, in order to avoid the spread of the virus. In addition, multidisciplinary work could be promoted, among the engineering and health sciences in the American Continent and Worldwide, through research, development and innovation projects in Biomedical Engineering, with the proposal of being ready to face a global and national emergency like the current Pandemic caused by SARS-CoV-2.